Analysis of Inpatient Bed Allocation Equity and Utilization in the City Community Health Service Center of China - 许静 吴妮娜 金生国 王芳 王云霞 刘利群 卢祖洵 (Journal of Huazhong University of Science and Technology. Medical sciences, 2010)
The objective of this study was to examine the inpatient bed （IB） allocation equity and utilization in Chinese city commtmity health service centers （CHSCs）. The data were derived from the Baseline Survey of National City Community Health Service System Building Project, which was conducted in 1917 CHSCs in 28 cities in 2007. The IB allocation was analyzed in terms oflB alloca- tion quantity and distribution equity, and the IB utilization was analyzed by the IB utilization rate and average length of stay of the CHSC inpatients. The results showed that 49.3% of the CHSCs were equipped with IB; averagely, there were 45 IBs per CHSC, 0.94 IBs per 1000 people, and 0.38 nurses and 0.57 doctors per IB; the IB Gini coefficient was 0.32; the IB utilization rate was 40.06%; and the average length of stay of inpatients was 12.24 days. The conclusions were that IB allocation among the population was equitable, but the number of nurse per IB was not up to the national standard; and the CHSC IB utilization was low as a whole, thus inpatient service was not the main health service for Chinese CHSCs.